2020
DOI: 10.15446/rfnam.v73n2.79552
|View full text |Cite
|
Sign up to set email alerts
|

The residual effect of metsulfuron on soybean tolerant and non-tolerant to sulfonylureas

Abstract: Metsulfuron is widely used for weed management; however, the residual effect on STS soybean cultivars is unknown. The objective of this work was to evaluate the residual effect of the herbicide metsulfuron on the BMX Garra RR2/STS and M 6410 IPRO (non-STS) soybean cultivars. The herbicide metsulfuron was applied at a rate of 2.4 g a.i. ha-1, in pre-planting of soybean plants. The design was completely randomized in a 2×5 factorial scheme with four replications (first factor: two soybean cultivars - STS and no-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The tolerant varieties, although declining from the control at the higher rates, maintained a significantly greater germination rate than the susceptible varieties. Silva et al (2020b) reported a comparison between the STS-tolerant cultivar BMX Garra RR2/STS and a susceptible cultivar, which demonstrated greater injury to dry weight for treatments planted 0-30 days after application of metsulfuron-methyl (Accurate). But at 45-60 days after application, there was no significant difference Crop Science in injury.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…The tolerant varieties, although declining from the control at the higher rates, maintained a significantly greater germination rate than the susceptible varieties. Silva et al (2020b) reported a comparison between the STS-tolerant cultivar BMX Garra RR2/STS and a susceptible cultivar, which demonstrated greater injury to dry weight for treatments planted 0-30 days after application of metsulfuron-methyl (Accurate). But at 45-60 days after application, there was no significant difference Crop Science in injury.…”
Section: Core Ideasmentioning
confidence: 99%
“…Silva et al. (2020b) reported a comparison between the STS‐tolerant cultivar BMX Garra RR2/STS and a susceptible cultivar, which demonstrated greater injury to dry weight for treatments planted 0–30 days after application of metsulfuron‐methyl (Accurate). But at 45–60 days after application, there was no significant difference in injury.…”
Section: Introductionmentioning
confidence: 99%